2009
DOI: 10.5021/ad.2009.21.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of 168 Korean Patients with Rosacea: The Sun Exposure Correlates with the Erythematotelangiectatic Subtype

Abstract: Background:Although rosacea is a chronic cutaneous inflammatory disorder that's commonly seen in adults, the etiology and pathogenesis of the illness remain unclear. A well established diagnostic classification and grading system may play a critical role in performing research and it would serve as a diagnostic reference in the clinical field. Objective: We sought to classify the patients with the new standard classification and grading system and we wanted determine the peculiar features and relationships of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
60
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 22 publications
7
60
2
1
Order By: Relevance
“…A previous study involving 168 subjects with rosacea found a significant association between the severity of ETR and OC, but no association between PPR and PHY. 15 However, in that study only seven (4Á2%) subjects had phymatous features, compared with 33 (24%) in the present survey. A recent review of rosacea indicates that flushing associated with this condition is not evanescent but prolonged and can persist for longer than 10 min.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…A previous study involving 168 subjects with rosacea found a significant association between the severity of ETR and OC, but no association between PPR and PHY. 15 However, in that study only seven (4Á2%) subjects had phymatous features, compared with 33 (24%) in the present survey. A recent review of rosacea indicates that flushing associated with this condition is not evanescent but prolonged and can persist for longer than 10 min.…”
Section: Discussioncontrasting
confidence: 72%
“…These findings concur with previous studies showing that persistent erythema was the most common of the four primary features. 15 We also observed that erythema was universally reported as the most bothersome feature of rosacea.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Previous studies have evaluated clinical differences and progression between rosacea subtypes [15,17]. A small proportion of subjects with ETR may progress to PPR and to PHY, whereas a small proportion of those with PPR may develop PHY.…”
Section: Discussionmentioning
confidence: 99%